2016
DOI: 10.1590/1980-5497201600040013
|View full text |Cite
|
Sign up to set email alerts
|

Diferenças regionais e fatores associados ao número de consultas de pré-natal no Brasil: análise do Sistema de Informações sobre Nascidos Vivos em 2013

Abstract: ABSTRACT:Objective: To investigate factors associated with seven or more prenatal visits, in Brazil, in 2013. Methods: Cross-sectional study from the database of Information System on Live Births. The association of explanatory variables was tested with prenatal visits by means of the analysis of single and multiple multinomial regressions. The spatial distribution of prenatal visits according to the Brazilian municipalities was also analyzed. Results: It was found that 2.7% of pregnant women attended no prena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0
17

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 23 publications
3
16
0
17
Order By: Relevance
“…Anjos and Boing [18] analyzed that the level of education was a factor significantly associated with the practice of an increased number of prenatal consultations (seven or more). Similarly, Joshi et al [25], in a study carried out in Nepal verified that as the level of education of pregnant women increased, their chances of having four or more prenatal consultations also increased, being seven times higher when compared to the extreme groups of schooling.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anjos and Boing [18] analyzed that the level of education was a factor significantly associated with the practice of an increased number of prenatal consultations (seven or more). Similarly, Joshi et al [25], in a study carried out in Nepal verified that as the level of education of pregnant women increased, their chances of having four or more prenatal consultations also increased, being seven times higher when compared to the extreme groups of schooling.…”
Section: Resultsmentioning
confidence: 99%
“…This finding was seen for all Brazilian regions, especially in the North, Northeast and South, where the chances of a C-section in women with a higher level of education were quite significant over the years (Table 3). The Northeast region, according to study by Silva et al [16], shows disparities in the efficiency of public spending and receive less public resources for health care compared to the Southeast, South and Midwest regions, as well as presenting lower health insurance coverage rates [1], fewer prenatal consultations by pregnant women, with inadequate prenatal care in less favored areas [18]. Therefore, these facts may lead to greater risks and/or maternal-infant complications during pregnancy due to the lack of adequate follow-up, resulting in the indication of C-sections to avoid more serious risks for mother and baby.…”
Section: Discussionmentioning
confidence: 99%
“…Using a cross-sectional approach, studies carried out in Brazil with regional 13 or national samples 10 have identified higher levels of schooling associated with greater likelihood of having the appropriate number of prenatal consultations. Studies have also found and described that increased uptake of prenatal care is more common among people with better living conditions and better jobs.…”
Section: Discussionmentioning
confidence: 99%
“…Aligned with the Brazilian Ministry of Health recommendations on resolute prenatal care [ 26 ] and the isolated capacity of MUAC and SBSF to detect the increase in amounts of maternal central fat, the inclusion of clinical anthropometry during the first 20 weeks of pregnancy can contribute to accurate maternal metabolic risk prediction. Thus, their complementary use in clinical practice is justified, as well as their possible inclusion in protocols for nutritional assessment during pregnancy.…”
Section: Discussionmentioning
confidence: 99%